2022
DOI: 10.1186/s12884-022-04616-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet, nutritional status and infant birth weight in Malaysia: a scoping review

Abstract: Background Women’s diet and nutritional status during pregnancy are important in influencing birth outcomes. We conducted a systematic scoping review of the best available evidence regarding dietary intake of Malaysian pregnant women, and the associations of maternal diet, anthropometry, and nutrition-related co-morbidities with the infant’s birth weight (IBW). The study objectives were to examine: (1) the adequacy of micronutrient intake among pregnant women; and (2) the association of materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…During pregnancy, the food intake of women in terms of quality and quantity is a well-recognized determinant of maternal and infant outcomes, such as birth weight, gestation length and gestational weight gain (10). However, less is known about the relationship between maternal chrononutrition characteristics with pregnancy and infant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, the food intake of women in terms of quality and quantity is a well-recognized determinant of maternal and infant outcomes, such as birth weight, gestation length and gestational weight gain (10). However, less is known about the relationship between maternal chrononutrition characteristics with pregnancy and infant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the relatively low awareness on vitamin D intake among antenatal mothers, which is related to lower educational background (Bukhary et al, 2016). In addition, the sun avoidant lifestyles and also Muslims who cover themselves (especially ladies) during outdoor activities have been shown to be related to vitamin D insufficiency (Mohamed et al, 2022). Meanwhile, majority of antenatal mothers in this…”
Section: Discussionmentioning
confidence: 89%
“…A healthy diet is important for the preservation of oral health and positive pregnancy outcomes. However, a scoping review reported that nutrient intake for most antenatal mothers, particularly iron, folate, vitamin D, and calcium were inadequate in urban and suburban areas of Malaysia (Mohamed et al, 2022). It is well established that nutrition and oral health has a bi-directional relationship in the general population (American Dental Association, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic factors also play a significant role in the effectiveness of family MUAC programs. Mohamed et al (2022) found that maternal factors such as high pre-pregnancy body mass index (BMI), excess gestational weight gain (GWG), and high blood glucose levels were associated with fetal macrosomia, while low pre-pregnancy BMI, inadequate GWG, intake of confectioneries and condiments, and high blood pressure were associated with low birth weight. Chitekwe et al (2018) found that long distances between home and treatment centers, lower MUAC at admission, or having diarrhea, vomiting, fever, or cough during the treatment episode were factors associated 2017) also found that the prevalence of stunting, underweight, and global acute malnutrition rates was high among children in Kwale County, Kenya, with male children being associated with a significantly higher prevalence of stunting than females, and the prevalence of underweight and stunting increasing with age.…”
Section: Literature Reviewmentioning
confidence: 99%